(untitled) (The Pakistan Development Review, 2008)
It is always a pleasure for me to participate in these annual meetings. The knowledge and the talent displayed are immense. The quality of discussion is high. I had never thought however that I would have the honor of delivering the Aalama Iqbal lecture. To prepare for this lecture I read extensively from Iqbal’s poetry. Of course I read in translation, but even so I was overwhelmed by the beauty of the ideas and the expression. My search for an apt couplet or set of lines for this paper was in vain. Iqbal was speaking to his people and although he was expansive in his view of society, it is still not meant for me to carry the word of Iqbal to you. Nevertheless I do display at the beginning of this paper three lines from Iqbal. He is clear on the importance of doing for oneself and for ones country. At least in the modern world ones efforts are so much more productive if government provides a favourable environment for individual effort. And he would embrace the brotherhood of mankind, leaving some potential for us to help each other. He was very clear that learning from the West was desirable, and he was very selective about that—science and technology in particular. My paper is about what government must do, and specifically the government of Pakistan must do, to create an environment in which not just a few gather dew but in which all people gather dew. As soon as ones concern encompasses the bulk of the population food security comes to the fore. My paper can be seen as addressing how all rural people can gather the dew. It has a prominent place for science and technology.